Synthesis of organic-inorganic hybrid nanocomposite material 9-hydroxy-9 fluorenecarboxylic acid intercalated into zinc-aluminium layered double hydroxide / Mohd Hafiz Abdul Razak - Abdul Razak, Mohd Hafiz (Faculty of Applied Sciences, 2009)
Synthesis of new hybrid nanocomposite material zinc-aluminium-9-hydroxy-9- fluorenecarboxylate was successfully accomplished by self assembly method with molar ratio of Zn to Al ; R= 2 at various concentration of 9-hydroxy-9-fluorenecarboxylate ranging from 0.2 M to 0.8 M . The pH of the synthesis was kept constant at 7.5. As a result of the successful intercalation of 9-hydroxy-9-fluorenecarboxylate anion into zincaluminium- layered double hydroxide, an expansion of the interlayer spacing from 8.9 Å in the layered double hydroxide to 14.3 Å in the zinc-aluminium9-hydroxy-9- fluorenecarboxylate nanocomposite could be observed in the PXRD diffractogram. The percentage loading of the guest anion, 9-hydroxy-9-fluorenecarboxylate in the layered double hydroxide was estimated to be about 76-78% (w/w) at the optimum condition